The Significance of Qualitative Research in Nursing Practice - Dara Abdulla Al-Banna (Hawler Medical University, 2018)
According to the World Health Organization, qualitative research aims to explore people's needs, values, perceptions and experiences of the world around them, including of health, illness, healthcare services, and more broadly of social systems and their policies and processes. Qualitative evidence is very important for understanding how, and whether, people perceive health interventions to be effective and acceptable or more fundamentally, whether they work. Qualitative evidence is also essential to understanding the factors affecting the application of health policies and interventions.